2017
DOI: 10.3390/su9081299
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Two Soil Fertility Indexes to Evaluate Paddy Fields for Rice Cultivation

Abstract: Abstract:Assessing soil fertility is essential to help identify strategies with less environmental impact in order to achieve more sustainable agricultural systems. The main objective of this research was to assess two soil fertility evaluation approaches in paddy fields for rice cultivation, in order to develop a user-friendly and credible soil fertility index (SFI). The Square-Root method was used as a parametric approach, while the Joint Fuzzy Membership functions as a fuzzy method with adapted criteria def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 26 publications
(20 reference statements)
0
10
0
Order By: Relevance
“…To explain the lack of specific rhizobia of A. farnesiana in the CE soil, the physicochemical characteristics of the soil were determined and only the macronutrients that estimate the degree of fertility of a soil were evaluated. It has been reported that the values of nitrogen, phosphorus and electrical conductivity are indicators of the fertility of a soil (Aprile & Lorandi 2012, Delsouz-Khaki et al 2017. Considering the values of the macronutrients, the CE soil was classified as a soil of low fertility because of its low amount of nitrogen and phosphate, and its low value of electrical conductivity.…”
Section: Discussionmentioning
confidence: 99%
“…To explain the lack of specific rhizobia of A. farnesiana in the CE soil, the physicochemical characteristics of the soil were determined and only the macronutrients that estimate the degree of fertility of a soil were evaluated. It has been reported that the values of nitrogen, phosphorus and electrical conductivity are indicators of the fertility of a soil (Aprile & Lorandi 2012, Delsouz-Khaki et al 2017. Considering the values of the macronutrients, the CE soil was classified as a soil of low fertility because of its low amount of nitrogen and phosphate, and its low value of electrical conductivity.…”
Section: Discussionmentioning
confidence: 99%
“…The low Organic-C at 400-800 masl is due to the lower altitude compared to an altitude of 1000-1400 masl [26]. High organic matter content not only provides nitrogen requirements for plants but also increases the water retention capacity of the soil and creates a favorable physical, chemical, and biological environment [27]. Soil organic matter has a very influential effect on the activity and diversity of microorganisms [28][29][30] involved in the degradation process of soil pollutants [31].…”
Section: Land Suitabilitymentioning
confidence: 99%
“…Assessment of Soil Fertility Index can help identify areas of problem or need appropriate special management (Bagherzadeh et al, 2018). Soil Fertility Assessment can provide information to estimate specific indicators of soil fertility to obtain the value of the soil fertility index that can be used to make a recommendation of soil fertility Management (Andrews, 2004;Khaki et al, 2017). In the soil fertility evaluation system, the weight determination of each index is a key factor that affects the accuracy of Evaluation (Plant, 2001;Mc Bratney et al, 2014;Chen et al, 2020).…”
Section: Introductionmentioning
confidence: 99%